In Silico Screening and In Vivo Evaluation of Potential CACNA2D1 Antagonists as Intraocular Pressure-Reducing Agents in Glaucoma Therapy - Hanxuan Li; Mohamed Moustafa Ibrahim; Hao Chen; Wei Li; Monica M. Jablonski (MDPI AG, 2021)
Glaucoma is a leading cause of permanent vision loss and current drugs do not halt disease progression. Thus, new therapies targeting different drug targets with novel mechanisms of action are urgently needed. Previously, we identified CACNA2D1 as a novel modulator of intraocular pressure (IOP) and demonstrated that a topically applied CACNA2D1 antagonist-pregabalin (PRG)-lowered IOP in a dose-dependent manner. To further validate this novel IOP modulator as a drug target for IOP-lowering pharmaceutics, a homology model of CACNA2D1 was built and docked against the NCI library, which is one of the world's largest and most diverse compound libraries of natural products. Acivicin and zoledronic acid were identified using this method and together with PRG were tested for their plausible IOP-lowering effect on Dutch belted rabbits. Although they have inferior potency to PRG, both of the other compounds lower IOP, which in turn validates CACNA2D1 as a valuable drug target in treating glaucoma.